Saluran dan Efisiensi Pemasaran Pisang Barangan di Kecamatan Siantar Martoba Kabupaten Pematangsiantar (Jurnal Agribisnis dan Agrowisata, 2026)
Channel and Marketing Efficiency of Berangan Bananas in Siantar Martoba District, Pematangsiantar Regency. Barangan Bananas are an agricultural commodity that is widely cultivated in Siantar Martoba District, Pematangsiantar Regency. This study aims to determine the marketing channels of Barangan Bananas, the efficiency of marketing channels based on marketing margins and farmer's share as well as obstacles encountered by farmers. The sample determination technique uses simple random sampling with a total sample of 33 farmers, while the determination of traders using the snowball sampling method is carried out by census. The results showed that there were four marketing channels for Pisang Barangan carried out by Banana Barangan farmers in Siantar Martoba District. The four marketing channels of Pisang Barangan are classified as efficient, but the marketing margin in marketing channel IV has the smallest margin value and the farmer's share of marketing channel IV has the highest percentage. The obstacles experienced by Banana Barangan farmers consist of cultivation/technical, social, and economic aspects. Banana Barangan farmers in Siantar Martoba District are advised to remain focused on using marketing channels I, II, and III because the sales volume covers 99.43% and the marketing channels are relatively efficient.
Keywords: Barangan Bananas; marketing funnel; marketing efficiency